Fate, time, and language : an essay on free will - Wallace, David Foster (Columbia University Press, 2011)
Ebook from IG Library; Includes bibliographical references and indexes; Fate, Time, and Language presents Wallace's brilliant critique of Taylor's work. Written long before the publication of his fiction and essays, Wallace's thesis reveals his great skepticism of abstract thinking made to function as a negation of something more genuine and real. He was especially suspicious of certain paradigms of thought-the cerebral aestheticism of modernism, the clever gimmickry of postmodernism-that abandoned "the very old traditional human verities that have to do with spirituality and emotion and community." As Wallace rises to meet the challenge to free will presented by Taylor, we witness the developing perspective of this major novelist, along with his struggle to establish solid logical ground for his convictions. This volume, edited by Steven M. Cahn and Maureen Eckert, reproduces Taylor's original article and other works on fatalism cited by Wallace. James Ryerson's introduction connects Wallace's early philosophical work to the themes and explorations of his later fiction, and Jay Garfield supplies a critical biographical epilogue.